Penguatan Strategi Edukasi Keluarga pada Era Digital - Pradana, Dominicus Wahyu; Yuniarto, Antonius; Lukito, Robertus Sigit Haribowo (LPPM Universitas Flores, 2022)
The big challenge facing parents today is about educating their children. This is due to generational differences that give rise to different characteristics and habits in each generation. The purpose of this community service is to foster a new mindset in educating children and being able to develop alternative ways of educating children to be more effective. The target of this activity is family in the Church of St. Paulus Juanda, Sidoarjo, totaling 52 people. After participating in this activity, the participants finally understood collectively the problems they faced as parents who educating millennial children. This awareness is followed by the development of a mindset that moves responses to the problem of educating children's character. There are similarities in responses even though the problems faced are quite complex. After listening to the speaker's presentation, each family formulates concrete intentions according to the child's uniqueness.